EL DERECHO HUMANO A LA RESISTENCIA LINGÜÍSTICA: THE HUMAN RIGHT TO LINGUISTIC RESISTANCE - Moncada Acosta, Alicia (2020)
Languages have historically been targets of any system that wants to impose itself and generate cultural hegemony. That is why -in the American continent- since the beginning of the colonial regime, indigenous languages were the object of persecution and suppression, a situation that was not mitigated with the constitution of national states. Precisely because languages are the foundation rocks of ethnicity, it has been essential for indigenous peoples to protect them from the onslaught of assimilationist and ethnocidal projects, being the protection of linguistic rights a useful tool for this purpose. The intention of this work is to present a review of the international standards built on cultural and linguistic protection, in order to expose the usefulness of the discourse and human rights protocols for the linguistic resistance and survival of indigenous peoples.